A Deep Eutectic Solvent as Leaching Agent and Electrolytic Bath for Silver Recovery from Spent Silver Oxide Batteries. Issue 1 (21st January 2021) - Sánchez-Ortiz, W.; Aldana-González, J.; Le Manh, Tu; Romero-Romo, M.; Mejía-Caballero, I.; Ramírez-Silva, M. T.; Arce-Estrada, E. M.; Mugica-Álvarez, V.; Palomar-Pardavé, M.
Abstract : It is shown for the first time that the deep eutectic solvent, DES, formed by acetylcholine chloride and urea can be successfully used for Ag recovery from the cathode powder of spent silver oxide batteries. This DES performs two important functions namely, as selective leaching liquor to extract Ag(I) ions from the remaining Ag2 O, leaving intact the metallic Ag in the solid phase, and as electrolytic bath for silver electrodeposition onto a glassy carbon electrode or graphite. Using potentiodynamic and potentiostatic electrochemical measurements, it was possible to quantify both: the Ag(I) leaching rate and the concentration of Ag(I) ions leached after 24 h. From this value, it was possible to estimate that about 7% of the original mass of the cathode powder corresponds to Ag2 O and the rest to metallic Ag. Moreover, from potentiostatic current density transients, recorded during Ag electrodeposition, it was shown, for the first time in this DES, that this process occurs via multiple 3D nucleation with diffusion-controlled growth and valuable practical information i.e. the diffusion coefficient of Ag(I) ions in this media was quantified. From scanning electron microscopy images and energy-dispersive X-ray spectroscopy, the morphology and composition of the resulting deposits were characterized.